Evaluation of Drug Planning and Procurement at UPT Babulu Health Center North Penajam Paser Regency - Bunga', Gerson; Syaodih, Erliany; Santoso, Budi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Medicine planning and procurement are two important steps in fulfilling the need of medicines in a certain unit of health service. Drug planning is a process of selecting drugs and health supplies to determine the type and amount of drug in order to meet drug needs at the puskesmas. Planning for drug needs at the UPT Babulu Health Center is still not in accordance with real needs. The objective of this research is to evaluate the planning and procurement of drugs at the UPT Babulu Health Center Penajam Paser Utara. This type of research is a qualitative research with in depth interview method, the data is collected by means of observation, documentation, and the validity of the data using triangulation techniques. There are 4 (four) informant, namely The Head of the Babulu Health Center , The Person in Charge of the Drug Warehouse of the Babulu Healt Center, The Head of the Pharmaceutical Installation and the Pharmacist of the Babulu Health Center. The result of the study showed that there was a shortage of medicines at the Babulu Health Center due to a mismatch between the demand from the Puskesmas and the amount distributed by supplier (Penajam Paser Utara Health Department) and the delivery time to the Puskesmas which was quite long. Drug planning using the ABC method is helfful in overcoming these problems, so that the drug shortage at the Babulu Health Center can be overcome